No man's land of violence : extreme wars in the 20th century - Lüdtke, Alf 1943-2019 Hrsg; Weisbrod, Bernd 1946-; Bessel, Richard 1948-; Göttinger Gespräche zur Geschichtswissenschaft (Göttinger Gespräche zur Geschichtswissenschaft, 2006)
The war of atrocities : murderous scares and extreme combat / Alan Kramer -- Endkampf 1918 and 1945 : German nationalism, annihilation, and self-destruction / Michael Geyer -- The war to end all wars : the shock of violence in 1945 and its aftermath in Germany / Richard Bessel -- The killing frenzy : wartime narratives of enemy action / Joanna Bourke -- War as work : aspects of soldiering in twentieth-century wars / Alf L(c)ơdtke -- Woman's place in the no man's land of violence : the Indian subcontinent, 1947-48 / Gyanendra Pandey -- Armed struggle and sectarian violence : South Africa and Northern Ireland compared / Janet Cherry -- Performing violence : soldiers, paramilitaries, and civilians in the twentieth-century Balkan wars / Wolfgang H(c)œpken -- Religious languages of violence : some reflections on the reading of extremes / Bernd Weisbrod